Remote learning for the beginning band trumpet student - Gifford, Jonathan B. (Kansas State University, 2021)
In this report, I will use video recordings as teaching demonstrations to assist beginning band trumpet students with the basic skills required to begin their journey in band. Through examples and demonstration, students will be afforded the opportunity to have a one-on-one lesson that will mold them in the areas of instrument care, proper posture and breathing techniques, and creating and developing their first sounds. The access to these video demonstrations affords the student the ability to repeat lessons and reference back to them as needed for mastery. Through this program, I have developed in self-evaluation as well as flexibility of an ever-changing learning environment. Remote learning is becoming more of necessity in education. Creating a video library with video demonstrations is not only something that will function in a remote learning environment; it will also allow students to begin development as they transition from elementary school to middle school. I have learned that developing a comprehensive approach to teaching partnered with a hands-on approach will have the most success for students. Videos can be re-evaluated and designed to accommodate what a “one size fits all” approach will not handle. Assessment for these videos can be utilized through video recordings of students demonstrating the tasks each video teaches as well as using zoom in a live time evaluation of the student. These methods of instruction have shown me that students do not always have to be directly in front of you to learn. Having remote access can still benefit the student’s ability to learn.
Keywords: Beginning trumpet; Embouchure; Beginning band; Mouthpiece buzzing; Buzzing